Alfalfa haylage for sows during gestation - Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Digestion and nitrogen retention studies suggest that three pounds of good quality alfalfa haylage dry matter and two pounds of a grain, mineral, and vitamin premix will meet the nutritional requirements of sows during gestation. Quality of the haylage is extremely important for sows. Third-cutting alfalfa had a higher digestible energy and digestible protein than did the more mature first-cutting haylage. The digestible energy of alfalfa haylage for sows was 954 to 1,096 Kcal/pound. Sows fed alfalfa haylage and ONLY ONE pound of a grain vitamin and mineral premix farrowed pigs that were lighter at birth than pigs farrowed from sows fed 4½ pounds of a corn-soy diet during gestation.
Keywords: Swine; Alfalfa; Gestation